2017
DOI: 10.1002/stc.2085
|View full text |Cite
|
Sign up to set email alerts
|

Wave-based SHM of sandwich structures using cross-sectional waves

Abstract: Summary The identification of structural damage in composite waveguides is a critical issue in aerospace and transportation industries. Frequently, these structures involve periodic patterns or dissipative components that considerably reduce the range, robustness, and available bandwidth of ultrasonic structural health monitoring techniques. On the other hand, wave‐based methods provide more accurate information on a defect's type, size, and location than modal analysis techniques. This paper focuses on a low‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The first positive peaks seen in each of the graphs indicate the arrival of the pressure pulse to the corresponding pressure monitoring location. The compression pulse subsequently propagates past the respective pressure monitoring locations s 1 ,s 2 ,s 3 ,s 4 ,s 5 , and s 6 . The first negative peaks shown at the various pressure monitoring locations are the times taken by the wave to travel to the pipe outlet and back to the corresponding pressure monitoring locations.…”
Section: Estimation Of Blockage Locations From the Predicted Pressumentioning
confidence: 99%
See 1 more Smart Citation
“…The first positive peaks seen in each of the graphs indicate the arrival of the pressure pulse to the corresponding pressure monitoring location. The compression pulse subsequently propagates past the respective pressure monitoring locations s 1 ,s 2 ,s 3 ,s 4 ,s 5 , and s 6 . The first negative peaks shown at the various pressure monitoring locations are the times taken by the wave to travel to the pipe outlet and back to the corresponding pressure monitoring locations.…”
Section: Estimation Of Blockage Locations From the Predicted Pressumentioning
confidence: 99%
“…They concluded that the classification resolution can reach a much as more than 99% for road cutters and 95% for overall. Droz et al proposed a way of using high‐order cross‐sectional waves (CSW) to increase the sensitivity of a low‐frequency guided wave method for structural health monitoring (SHM). They conducted a diffusion analysis through three types of defects, and they show that waveguide's finite section can be used to exploit the reflection characteristics of CSW.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the development of damage detection methods based on different and ample varied nondestructive techniques. For example, some recent techniques are based on the use of guide waves, 2 solitary waves, 3 Lamb waves, 4,5 the change of the plate electromechanical impedance, 6 or the ultrasonic dispersive properties, 7 exploring the flexural 8 and cross-sectional waves 9 or applying thermographic analysis. [10][11][12][13] Additionally, a recent concern has arisen regarding the reliability of nondestructive techniques to sizing and locating damage; see, for instance, Aldrin et al, 14 where a regression analysis is proposed to address the issue.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a dynamic homogenization technique is developed that exploits WFEM framework in a CPA context to create an equivalent media in order to overcome these issues. In the proposed technique, the Diffusion Matrix Model (DMM) [22,23,24], which is an highly effective numerical technique to determine the local scattering properties of Bloch waves propagating through a FE-modelled interface, is used.…”
Section: Introductionmentioning
confidence: 99%